2017
DOI: 10.1161/jaha.116.004297
|View full text |Cite
|
Sign up to set email alerts
|

Performance of AHEAD Score in an Asian Cohort of Acute Heart Failure With Either Preserved or Reduced Left Ventricular Systolic Function

Abstract: Background AHEAD (A: atrial fibrillation; H: hemoglobin; E: elderly; A: abnormal renal parameters; D: diabetes mellitus) score has been related to clinical outcomes of acute heart failure. However, the prognostic value of the AHEAD score in acute heart failure patients with either reduced or preserved left ventricular ejection fraction (HFrEF and HFpEF) remain to be elucidated.Methods and ResultsThe study population consisted of 2143 patients (age 77±12 years, 68% men, 38% HFrEF) hospitalized primarily for acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…We showed that the GWTG‐HF risk score would be useful for prognostic prediction after hospitalization in both patients with HFpEF and patients with HFrEF. Although Chen et al reported that the AHEAD score was useful in predicting long‐term mortality in an Asian cohort with HFrEF or HFpEF,16 we could not indicate the preference of the GWTG‐HF risk score compared to the AHEAD score in this study. Moreover, we derived the modified GWTG‐HF model on the basis of the multivariable Cox proportional hazard regression analysis, and this model demonstrated significantly higher C‐statistics in both all‐cause deaths and cardiac events.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We showed that the GWTG‐HF risk score would be useful for prognostic prediction after hospitalization in both patients with HFpEF and patients with HFrEF. Although Chen et al reported that the AHEAD score was useful in predicting long‐term mortality in an Asian cohort with HFrEF or HFpEF,16 we could not indicate the preference of the GWTG‐HF risk score compared to the AHEAD score in this study. Moreover, we derived the modified GWTG‐HF model on the basis of the multivariable Cox proportional hazard regression analysis, and this model demonstrated significantly higher C‐statistics in both all‐cause deaths and cardiac events.…”
Section: Discussioncontrasting
confidence: 57%
“…Recently, several risk stratification scores using various parameters have been reported for the prediction of all‐cause mortality, sudden cardiac death, and cardiovascular events in patients with HF 9, 10, 11, 12, 13, 14, 15, 16. For example, the AHEAD (atrial fibrillation, hemoglobin, elderly, abnormal renal parameters, diabetes mellitus) score was established for long‐term risk prediction in acute HF 15.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The discrimination and calibration of these risk scores have been well validated in Asian patients with AHF. 17,18 Therefore, the GWTG-HF risk score and AHEAD score were used as adjustment variables in the multivariable prognostic model. Survival was evaluated using the Kaplan-Meier method and compared using the log-rank test.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, echocardiographic variables including LVEF, left atrial diameter (LAD), mitral early diastolic inflow velocity (E), mitral late diastolic inflow velocity (A), mitral annular early diastolic velocity (e 0 ), and deceleration time of mitral early diastolic inflow (DCT) were measured. The AHEAD score was used for risk assessment and was calculated by assigning one point to each of the following factors: A: atrial fibrillation, H: haemoglobin <13 g/dL for men and 12 g/dL for women, Elderly (age > 70 years), A: abnormal renal parameters (creatinine > 130 μmol/dL) and D: diabetes mellitus [20].…”
Section: Patient Characteristicsmentioning
confidence: 99%